(untitled) - Bass, Rick; 1958- (University of Texas Press, 2012)
"In November, countless families across Texas head out for the annual deer hunt, a ritual that spans generations, ethnicities, socioeconomics, and gender as perhaps no other cultural experience in the state. Rick Bass's family has returned to the same hardscrabble piece of land in the Hill Country--"the Deer Pasture"--for more than seventy-five years. In A Thousand Deer, Bass walks the Deer Pasture again in memory and stories, tallying up what hunting there has taught him about our need for wildness and wilderness, about cycles in nature and in the life of a family, and particularly about how important it is for children to live in the natural world.. The arc of A Thousand Deer spans from Bass's boyhood in the suburbs of Houston, where he searched for anything rank or fecund in the little oxbow swamps and pockets of woods along Buffalo Bayou, to his commitment to providing his children in Montana the same opportunity--a life afield--that his parents gave him in Texas. Inevitably this brings him back to the Deer Pasture and the passing of seasons and generations he has experienced there. Bass lyrically describes his own passage from young manhood, when the urge to hunt was something primal, to mature adulthood and the waning of the urge to take an animal, his commitment to the hunt evolving into a commitment to family and to the last wild places."--
"A definitive and eloquent book about the Texas deer hunting experience and the lessons it teaches about the cycles of life in nature and in a family"--
Machine generated contents note: My Naturalist Mother -- Records -- The Other Fort Worth Basses -- On Willow Creek -- Deer Camp -- This Year's Hunt -- The Deer Pasture -- The Silent Language -- A Texas Childhood -- Colter's Creek Buck -- Aoudads -- Mary Katherine's First Deer -- Credits.
Keywords: Bass, Rick; 1958-; SPORTS & RECREATION / Hunting; Texas; Anecdotes; Deer hunting; Big game hunters; History; Deer hunting; Texas; Biography; HISTORY / United States / State & Local / Southwest (AZ, NM, OK, TX); Texas